Joint Optimization of Pricing and Inventory for Cross-Border E-Commerce Retail Export Supply Chains, Considering Export Tax Rebates and Stochastic Demand - Li, Fuchang; Jiang, Zhe; Hu, Xiaohui (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper investigates a cross-border dual-channel supply chain involving domestic manufacturers and foreign retailers. The supply chain integrates wholesale and online sales channels managed by domestic manufacturers with traditional retail channels operated by foreign retailers. The Chinese government provides export tax rebates to manufacturers to stimulate international sales, while foreign import tariffs influence pricing and demand dynamics. Consumer purchasing behavior in traditional retail channels is influenced by inventory levels. Excess inventory often triggers intensified promotional efforts by sales staff. The interaction between domestic manufacturers and foreign retailers is modeled as a Stackelberg game, with random demand following a Poisson distribution. The findings reveal that, under certain conditions, an increase in the export tax rebate rate reduces wholesale, direct sales, and distribution prices, which in turn boosts order volumes from retailers. Similarly, higher retail import tariffs can lower wholesale and direct sales prices, although the distribution price varies based on specific factors, ultimately increasing retailer order volumes. In contrast, an increase in wholesale import tariffs results in lower prices across all channels and reduced retailer order volumes. Additionally, when consumer preference for online shopping increases, wholesale prices decrease, direct sales prices rise, distribution prices drop, and retailer order volumes decline. Numerical simulations provide strategic insights for optimizing profitability in cross-border dual-channel supply chains. These insights contribute to greater supply chain stability, alleviation of domestic overcapacity issues, and promotion of international cooperation for mutual benefits. This research offers both theoretical and practical guidance for multinational firms aiming to refine wholesale and inventory strategies in tariff-sensitive environments. It highlights pathways to enhance resilience and expand operations in global markets.